The Outbreak of Novel Coronavirus Disease (COVID-19) Pandemic: Consequences on Public Mental Health - Hossain, S. M Khaled; Akhter, Mahfuza (Journal of Brain Sciences, 2020)
The purpose of the current study is to investigate the impact of novel coronavirus disease (COVID-19) pandemic on the mental health of people living in Bangladesh. Data required for conducting the study were collected from 1000 respondents of Bangladesh especially in reference to Dhaka and Mymensingh districts through serving a structured questionnaire. The sample size was selected by using convenient sampling technique. DASS-21 was used to assess the mental health indicated by level of depression, anxiety and stress among the target respondents. The study found that level of depression; anxiety and stress differ in accordance with the gender, age, marital status, education, employment and professional status. The research result showed that, there is significant difference among gender, age, marital status, educational qualification and professional status in regard to depression, anxiety and stress level whereas there is no significant difference among employment status in regard to depression, anxiety and stress level of the respondents.